The focus of autonomy in the management perspective of special autonomy funds - Mahfud, Faisal A. Rani, Rizanizarli, Ilyas, Fikri, (Opción, 2020)
This study aims to identify the direction of the focus of autonomy in the implementation of special autonomy authority from the perspective of the management of special autonomy funds via comparative qualitative research methods. The results showed that the authority to manage special autonomy funds was not specified in detail. In conclusion, from the percentage of allocation of funds, 60% (sixty percent) for the Government of Aceh and 40% (forty percent) for Regency/cities, the focus of autonomy in the management of special autonomy funds lies with the Government of Aceh.